2017
DOI: 10.1017/s0267190517000149
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Linguistic Purism in Dual Language Bilingual Education: A Case Study of Hebrew in a New York City Public Middle School

Abstract: Dual language bilingual education (DLBE) programs, in which students are taught language and academic content in English and a partner language, have dramatically grown in popularity in U.S. schools. Moving beyond the teaching of Spanish and Chinese, DLBE programs are now being offered in less commonly taught languages and attracting new student populations. Based on qualitative research conducted in a New York City public middle school that recently began a Hebrew DLBE program, we found that this program, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In the future, we will witness an increasing number of studies with various foci in this area. Regarding the countries of the study, English-dominant countries, especially the US with 11 articles (e.g., Menken & Avni, 2017;Rowe, 2019), account for the biggest slice of the cake. Other regions include Singapore , Zimbabwe (Mazuruse & Mberi, 2012), Sweden (Dávila & Bunar, 2020), Italy (Ghimenton, 2015) and Bolivia (Hornberger & Swinehart, 2015), suggesting the strong need to further our knowledge in contexts where English is not the official language or widely spoken.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, we will witness an increasing number of studies with various foci in this area. Regarding the countries of the study, English-dominant countries, especially the US with 11 articles (e.g., Menken & Avni, 2017;Rowe, 2019), account for the biggest slice of the cake. Other regions include Singapore , Zimbabwe (Mazuruse & Mberi, 2012), Sweden (Dávila & Bunar, 2020), Italy (Ghimenton, 2015) and Bolivia (Hornberger & Swinehart, 2015), suggesting the strong need to further our knowledge in contexts where English is not the official language or widely spoken.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies identify the application of translangauging materials (e.g., Menken & Avni, 2017;Hornberger & Swinehart, 2012). It is assumed that the materials provided for students are different according to their language proficiency and age.…”
Section: Translanguaging Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Principals play a powerful role in any school—creating school culture, shaping teaching and learning, and charting the direction of program development (Bryk, Sebring, Allensworh, Easton, & Luppescu, 2010; Darling‐Hammond, LaPointe, Meyerson, Orr, & Cohen, 2007)—as well as interpreting and enacting policies created at larger scales (Ball et al, 2012). In DL schools, based on their knowledge and beliefs about language and learners, principals make decisions that can sustain or dismantle DL programs, as well as maintain or disrupt the larger status quo (Alanís & Rodríguez, 2008; DeMatthews & Izquierdo, 2018; Menken, 2017; Theoharis & O’Toole, 2011). Souto‐Manning, Madrigal, Malik, and Martell (2016) argued that all principals, but in particular DL principals, must therefore demonstrate “courageous leadership,” or the ability to navigate policy pressures from outside the school—from explicit English‐only policies to implicit nudges toward English through tools like state assessments—in ways that do not compromise the mission of their programs (e.g., Izquierdo, DeMatthews, Balderas, & Gregory, 2019; Menken & Solorza, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Hebrew education in the United States also reveals a distinctly novel learning context that warrants the attention of applied linguists: the teaching and learning of religious languages in secular educational settings. Along with Kate Menken, I have been studying the phenomenon of the expansion of dual language bilingual education programs in New York City (Menken & Avni, ). Focusing on a Hebrew–English program at a public middle school in Brooklyn, our study has shown that Hebrew is utilized to meet varying and overlapping communal needs, which include religious identification and nationalistic affiliations, as well as pragmatic desires such as access to a neighborhood school that offers a strong secular academic education.…”
mentioning
confidence: 99%